O090 The Sweet approach to oesophagectomy is still a valid surgical approach seldom used in the UK. (22nd July 2022) - Ammar, A; Paul, M; El-Sharkawy, A; Leeder, P; Bohra, A; Awad, S; Iftikhar, S
Abstract: Introduction: The left thoracophrenotomy approach to oesophagectomy or Sweet Oesophagectomy (SO) for oesophageal cancer is performed by many centres worldwide but seldom used in UK, owing to concerns over extent of lymphadenectomy compared with Ivor-Lewis oesophagectomy (ILO) approach. This study aims to compare oncological and clinical outcomes following the Sweet approach with ILO. Methods: A retrospective, single centre study was conducted, analysing all patient data following the SO approach and ILO for oesophageal cancer between August 2012 - March 2021. Results: The total number who underwent the Sweet (SO) operation and ILO was 72 and 197 patients respectively.91.7% vs 80.2%, p =0.071 were distal oesophageal tumours. Median lymph node count were 22 and 23 respectively, p =0.980. The Sweet was associated with 69.4% circumferential, 94.4% proximal and 95.8% distal R0 resections compared with 72.6% ( p =0.365, 98%( p =0.132) and 96%( p =0.330) with ILO resection, respectively. Median operative time was 169 vs. 301 minutes for Sweet and ILO respectively, p< 0.001. The overall complication rate was 29.2% with the Sweet and 45.7% with ILO, p =0.015, including, Anastomotic leaks 0 vs. 11, p =0.041 And return to theatre 1 vs. 22, p =0.04. The 30, 90 day and 5-year survival was 100% vs. 99%( p =0.391), 98.6% vs. 95.9% ( p=0.281) & 51.4% vs. 50.3% ( p=0.869 ), respectively. Conclusion: The Sweet procedure was associated with comparable oncological efficacy and survival to ILO. Furthermore, was associated with significantly shorter operative time and lower complication rates, therefore should be considered in selected cases. Take-home message: Left thoracotomy oesophagectomy remains an appropriate option with significantly better results in our centre, in the management of lower oesophageal and junctional carcinoma as compared to ILO. Having a reduced hospital stay and operative time may be more favourable in more frail patients with distal and junctional oesophageal tumours.